Type I interferon promotes cell‐to‐cell spread of Listeria monocytogenes. (10th October 2016) - Osborne, Suzanne E.; Sit, Brandon; Shaker, Andrew; Currie, Elissa; Tan, Joël M.J.; van Rijn, Jorik; Higgins, Darren E.; Brumell, John H.
Summary: Type I interferons (IFNs) play a critical role in antiviral immune responses, but can be deleterious to the host during some bacterial infections. Listeria monocytogenes ( Lm ) induces a type I IFN response by activating cytosolic antiviral surveillance pathways. This is beneficial to the bacteria as mice lacking the type I IFN receptor (IFNAR1 −/− ) are resistant to systemic infection by Lm . The mechanisms by which type I IFNs promote Lm infection are unclear. Here, we show that IFNAR1 is required for dissemination of Lm within infection foci in livers of infected mice and for efficient cell‐to‐cell spread in vitro in macrophages. IFNAR1 promotes ActA polarization and actin‐based motility in the cytosol of host cells. Our studies suggest type I IFNs directly impact the intracellular life cycle of Lm and provide new insight into the mechanisms used by bacterial pathogens to exploit the type I IFN response.